Isolation of Flavonoid Compounds and Anti-Cholesterol Test of Dutch Teak Leaf Extract (Guazuma ulmifolia Lamk.) - Parbuntari, Hesty; Yuliandari, Fadhira; Martha, Rahma Diyan (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Dutch teak (Guazuma ulmifolia Lamk.) is a tree originating from Latin America (Brazil and Mexico). The results of the phytochemical test showed that Dutch teak leaves positively contained flavonoids, alkaloids (Dragendorff reagent), steroids, and saponins. The purpose of this study was to characterize the flavonoid compounds and test the anti-cholesterol properties of Dutch teak leaf extract. Flavonoid characterization methods used Mg-HCl (yellow), H2SO4 (reddish orange), NaOH (yellow), KKt-2A, UV-Vis, and FT-IR reagents. Anti-cholesterol test using the Lieberman-Burchard method. The flavonoid crystals obtained were in the form of amorphous crystals of 0.1047 grams. In KKt-2A there is a change in color from yellow to greenish yellow when viewed with a UV lamp. The UV-Vis spectrophotometer has an absorption wavelength of 326 nm. The results of FT-IR analysis showed the presence of functional groups: OH, CH, C=O, C=C, and COC. Based on these data it can be concluded that the isolated flavonoids are in the form of amorphous crystals which belong to the flavone class with the name 5,7,4' - Trihydroxyflavone-6-Prenyl. The results of the cholesterol reduction test stated that Dutch teak leaves could be anti-cholesterol as seen from the absorbance value being smaller and the percentage of anti-cholesterol activity being greater.